Studies On The Pathogenesis Of Contagious Ecthyma In Goats And Sheep - Ismail, Roshidah (1994)

(untitled)
Local contagious ecthyma viruses isolated from sheep (Lb) and goats (GV 1 and GV 2) were used in a series of infection trials in kids and lambs to compare the pathogenesis, virus virulence and host susceptibility. Caprine contagious ecthyma isolate (GV 1) was able to establish infection in kids and lambs, producing typical lesions. When rechallenged, the infected kids and lambs developed rapid but milder lesions followed by rapid resolution. The clinical and histopathological changes in the primary and secondary infections were similar but were more severe in the former. The third infection, however, failed to establish any lesions. Secondary bacterial infection appeared to have complicated the contagious ecthyma lesions resulting in a marked reduction in body weight and occasional death. The inoculation of Corynebacterium pyogenes into the contagious ecthyma lesions resulted in much more severe lesions resembling those observed in field cases of complicated contagious ecthyma. This finding suggests that in natural cases, contagious ecthyma virus probably acts synergistically with other agents to produce severe and generalised lesions. Although the kids and lambs appeared to have similar disease, the kids developed more severe lesions. Severity of the lesions produced were compared statistically between the viral isolates and between the animal species. The caprine GV 2 isolate was found to produce lesions in both kids and lambs with similar severity whereas the ovine isolate (Lb) produced milder lesions in lambs but severe lesions in kids. These observations correlated well with the development of antibody response. In general, the lambs showed better antibody response than the kids, reaching significantly high level on day twenty-two, coinciding with recovery from the disease. The kids infected with Lb virus responded poorly leading to the severe disease and longer recovery period.